Proses Transaksi Pada Sistem Informasi Akuntansi Serta Implementasinya Pada Perbankan Syariah - Harianto; Rika Lidyah (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study examines the transaction process in the accounting information system and its implementation in Islamic banking, answering these problems. The author uses this type of research including library research. Library research is a type of research conducted by reading books, journals, or magazines and other data sources to collect data from various literature, both libraries and other places. In this study, the author determines the library research method because there are at least several reasons underlying it. Islamic Bank is a bank based on the principles of partnership, justice, transparency, and universality which are implemented in the form of prohibition of usury in its various forms, Accounting Information from several experts, including According to Nugroho Widjayanto Accounting Information System as follows: "Accounting Information System is a composition of various forms of records, equipment, including computers and equipment and communication tools, implementing personnel and reports that are closely coordinated which are designed to transform financial data into financial information needed by management" The use of accounting information systems also makes technological growth better in the Islamic banking sector, this can be a reason for customers to move from conventional banks to Islamic banks, because it is based on the accounting information system used.